PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN KOMUNIKASI ASERTIF SISWA SMA NEGERI 5 PEKANBARU TAHUN PELAJARAN2015/2016 - Arlizon, Raja; Yakub, Elni; ', Asrul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Communication is a necessity for humans because it is a need to establish a relationship with one another. Therefore, humans are required to skilled in communicating. The desired communication certainly assertive communication so that both parties feel comfortable doing the communication. Furthermore, in this study uses group counseling services as an independent variable (X). The purpose of this study was to determine the effect of Guidance Services Group Against Assertive Communication Students SMAN 5 Pekanbaru. This type of research that is in use is a real-experimental with patterns pretest-posttest control group design. The subjects were students of class IX IA which has a low assertive communication numbered 20 people. Based on the results obtained by processing data of significant figures (Asymp. Sig) 0,005 with alpha (Î±) of 0.05, it can be concluded 0,005 <Î± (0.05) which means that Ha Ho accepted and rejected, so "There are differences in the level of assertive communication before and after group counseling services. "From the SPSS version 16 obtained a correlation coefficient of 0.691 / r = r2 = 0.47 the 0691 then it can be concluded that the influence of group counseling to students assertive communication is 47%.Keywords : Guidance group , assertive communication.